Literature Review: Health Impact of Coal Combustion Emissions in Power Plant on Adult Respiratory Systems - Basuki Rachmat; Cita Fitria Puri; Elvi Sahara Lubis; Endang Krisnawaty; Lailatul Qomariyah; Widyana Siregar (Universitas Airlangga, 2021)
Introduction: Coal-fired power plants contribute to air pollution emissions of nearly one-third of global SO2 , 14 % of NOx , and 5 % of PM2.5. This condition could worsen adults' respiratory health who live close to power plants; WHO estimates that COPD and LRTI cause around 18% of premature deaths related to outdoor air pollution. This literature review aims to conduct a systematic review of the health impacts of coal-fired power plant emissions on adults' respiratory systems and explore what risk factors lead to decreased lung status. Also, to answer how risk factors influence decreased lung function in adults' respiratory system from coal-fired power plants' emissions. Discussion: This study used a literature study method using an online database to of various research data sources with the same topic. The searching of articles was performed based on the inclusion criteria. From an initial collection of 468 articles, after screening and considering its feasibility, four articles were obtained to serve as material for the final systematic review. The literature review showed that there had been a change in lung function of respiratory system of adults due to long-term exposure to emissions from coal-fired power plants. Factors that influence decreased lung function in adults were NOx and SO2 exposure levels, residence distance, wind direction, age, and smoking status. Conclusion: Future research should focus on improving models for assessing exposure to NOx , SO2 , PM10 and PM2.5, considering age and smoking habits in evaluating lung function.